Improving Vocabulary Skills of Kindergarten Students Through a Multi-Tier Instructional Approach. (January 2015) - Cuticelli, Mari; Coyne, Michael D.; Ware, Sharon M.; Oldham, Ashley; Loftus Rattan, Susan
There is a growing need for the inclusion of direct, explicit vocabulary instruction in the early elementary grades. Young children are entering school with a wide range of early literacy experiences, including vocabulary knowledge. Those students who are limited in their vocabulary knowledge are at a greater risk for later language and reading difficulties. When providing intensive vocabulary instruction to students who are at risk for language and reading difficulties, it is important to use features of effective instruction and intervention, including (a) direct, explicit instruction that includes extensive teacher modeling; (b) teacher and material scaffolding that carefully controls the level of task difficulty (e.g., moving from easier to more difficult tasks throughout the instruction); and (c) numerous practice opportunities with immediate and specific feedback.